What are the regulatory targets for intervention in assimilate partitioning to improve crop yield and resilience? - Paul, Matthew J. (Journal of plant physiology, 2021)
Sucrose utilisation for the synthesis of cellular components involved in growth and development and the accumulation of biomass determines diversity in the plant kingdom; sucrose utilisation and partitioning also underpin crop yields. As a complex process the use of sucrose for the partitioning of plant products for yield is decided by the interaction of several regulatory hubs and the integration of metabolism and development. Understanding the regulation of assimilate partitioning has been a grand challenge in plant and crop science. There are emerging examples of genes and processes that appear important for assimilate partitioning that underpin yield in crops and which are amenable to intervention. Enzymes of carbon metabolism were some of the first targets in attempts to modify assimilate partitioning at the beginning (source) and end (sink) of the whole plant assimilate partitioning process. Metabolic enzymes are subject to regulatory and homeostatic mechanisms, a key factor to consider in modifying assimilate partitioning. Trehalose 6-phosphate, as a sucrose signal, may represent a special case in its ability to regulate and coordinate source and sink processes. This review summarises recent progress in understanding the underlying regulators of assimilate partitioning and the current and potentially most promising routes to crop yield enhancement with a main focus on cereals. A framework for how source-sink may regulate whole plant assimilate partitioning involving a few key elements and the central importance of reproductive development is presented.